2016
DOI: 10.1017/s1047951116001281
|View full text |Cite
|
Sign up to set email alerts
|

Can whole-blood parameters be used in follow-up of children with rheumatic valvular heart disease?

Abstract: This is the first study in children with rheumatic heart disease that demonstrated significantly increased red blood cell distribution width, platelet distribution width, and mean platelet volume levels, as well as evaluated all three parameters together. Furthermore, red blood cell distribution width values in the chronical period of acute rheumatic fever, due to the positive correlation with the other chronic inflammatory markers, may help make the diagnosis in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Chiu-Braga et al also reported high levels of hs-CRP in chronic rheumatic valve disease (26). Karpuz et al observed that the CRP level was higher in patients with chronic RHD compared with the control group, and they suggested that this increase was an indicator of continuing inflammation (27). We also found that hs-CRP levels were significantly higher in patients with RHD than the control group.…”
Section: Discussionsupporting
confidence: 73%
“…Chiu-Braga et al also reported high levels of hs-CRP in chronic rheumatic valve disease (26). Karpuz et al observed that the CRP level was higher in patients with chronic RHD compared with the control group, and they suggested that this increase was an indicator of continuing inflammation (27). We also found that hs-CRP levels were significantly higher in patients with RHD than the control group.…”
Section: Discussionsupporting
confidence: 73%
“…A low mean platelet volume is usually related to an inflammatory state. 3,5,6 To our knowledge, no study has been conducted on the correlation of neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio and mean platelet volume with severity of carditis in rheumatic fever at Sanglah Hospital, Denpasar. Our study thus aimed to investigate the correlation of neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio and mean platelet volume with severity of carditis in children with rheumatic fever.…”
mentioning
confidence: 99%